Antihyperglycemic and antioxidant activity of Bajakah herbal tea made from Bajakah rod-Tikung honey-Amblycarpa lime (jeruk Sambal) [Aktivitas antihiperglikemia dan antioksidan minuman teh herbal Bajakah yang dibuat dari madu Tikung-batang Bajakah-jeruk Sambal] - Marina, Aristawipana; Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Hyperglycemia is characterized by elevated blood glucose levels, defined as instant blood glucose exceeding 200 mg/dL or fasting blood glucose surpassing 126 mg/dL. This condition has the potential to increase free radicals in the body. Using herbal ingredients or herbal drinks can also be a way to control blood glucose and free radicals. The Uncaria genus has functional anti-diabetic properties because it contains alkaloids and flavonoid compounds with antihyperglycemic and antioxidant effects. This study aimed to measure the antioxidant and antihyperglycemic potential of bajakah herbal tea with its raw materials (bajakah wood extract, honey, and Amblycarpa lime (jeruk Sambal)). The formulation of Bajakah herbal tea consists of 19.32 g Amblycarpa lime (jeruk Sambal), 46.38 g Bajakah rod extract, and 57.97 g honey. Antioxidant activity was achieved using the 2,2-diphenyl-1-picrylhydrazyl or DPPH method, and antihyperglycemic methods were used, such as the Oral Glucose Tolerance Test (OGTT). Physical characteristics are also tested for pH, color, and total dissolved solids. Data was analyzed using one-way ANOVA. The results showed that the combination of Bajakah-based herbal drinks, Bajakah herbal tea (123.67 g or equivalent to a carbohydrate content of 50 g), and the single preparation did not have antihyperglycemic activity. However, bajakah herbal tea has the highest antioxidant activity compared to its raw materials.